MAGNETISM, SUPERCONDUCTIVITY, AND THE METAL NONMETAL TRANSITION IN THE SPINEL LIAL-3+XTI2-XO4, LICR-3+XTI2-XO4 - Lambert, P; Edwards, P; Harrison, M (1990)
In the LiMxTi2-xO4 (M = Cr3+, Al3+) spinel solid solution systems, the M3+ cations substitute at the octahedral sites and thus directly interact with the titanium 3d conduction electrons. The effect is dramatically illustrated in the chromium series where superconductivity is supressed completely at 2.5% Cr3+ substitution by a magnetic impurity effect. Infrared transmission measurements indicate a metal-nonmetal transition (MNMT) in LiCrxTi2-xO4 at 0.33 < x < 0.40. In the aluminum series, the superconducting transition temperature Tc persists at a high value (> 6 K) to x = 0.33, where a MNMT is proposed. Percolation, disproportionation, and conduction electron concentration are briefly discussed as possible contributing mechanisms for the MNMT in the cation-substituted LiMxTi2-xO4 (M = Li+, Al3+, Cr3+) system. © 1990.